Proteomic study of the effect of metformin on C. albicans. Issue 12 (17th December 2021) - Mascaraque, Victoria; Navas, Cristina; Hernaéz, María Luisa; Gil, Concha; Molero, Gloria
Abstract : Fungal infections are a global health problem. Of them, those produced by Candida albicans are the most important, with a reduced arsenal of antifungals and an increasing problem of antifungal resistance. Thus, the discovery of new antifungal targets and drugs remains interesting. Metformin is a biguanide administered as a first-line treatment for Type II Diabetes Mellitus and it has recently been published its anti-Candida action, especially against C. glabrata, and its synergistic effect with other antifungals. Our studies of the effect of metformin on C. albicans have revealed an inhibition of growth, filamentation and other phenotypes important for virulence. Although metformin has been described as an AMPK agonist, its mechanism of action is partly unknown. To deepen into the anti-Candida mechanism of action, we have addressed the differential proteomic study. A set-up of the conditions for the proteomic study has been carried out, fixing a concentration of 50mM of metformin, 6 h of treatment at 37°C in RPMI medium and with 60 rpm of agitation. The proteomic study using the Labelfree technique and 4 biological replicas, allowed the identification and quantification of a total of 1899 proteins, 206 of them presenting differences in abundance due to metformin exposure. Of these, 127 increased and 79 decreased due to the action of the drug. The most relevant functions of these proteins are related to antifungal response, filamentation, biofilm formation and metabolism, being 9 essential proteins for the microorganism that could be new antifungal targets.